2015
DOI: 10.1103/physrevb.91.075401
|View full text |Cite
|
Sign up to set email alerts
|

Pt atoms adsorbed onTiO2(110)(1×1)studied with noncontact atomic force microscopy and first-principles simulations

Abstract: We have studied the local properties of single Pt atoms adsorbed on hydroxylated TiO 2 (110)-(1 × 1) by combining noncontact atomic force microscopy (nc-AFM) and first-principles calculations. Room-temperature high-resolution nc-AFM images for the most frequently observed contrast modes reveal bright and elongated protrusions that can be traced back to the Pt atoms, and that are centered on the fivefold coordinated titanium rows, confined between two bridging oxygen rows. These observations are in line with th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 36 publications
0
16
0
Order By: Relevance
“…The Au/TiO 2 interface has been the subject of theoretical and experimental investigation. Theoretically, metal–semiconductor contact theory 14 and density functional theory 15 are most frequently employed. On the experimental side, ultrahigh vacuum studies using scanning tunneling microscopy and atomic force microscopy (AFM) have been used for atomic-scale characterization of TiO 2 sensitized with metal clusters 16 , 17 and with organic dyes used in solar cells, 18 which contributed to our current knowledge of charge transfer in model metal/TiO 2 (110) systems, 19 including Pt 20 and small Pt clusters.…”
Section: Introductionmentioning
confidence: 99%
“…The Au/TiO 2 interface has been the subject of theoretical and experimental investigation. Theoretically, metal–semiconductor contact theory 14 and density functional theory 15 are most frequently employed. On the experimental side, ultrahigh vacuum studies using scanning tunneling microscopy and atomic force microscopy (AFM) have been used for atomic-scale characterization of TiO 2 sensitized with metal clusters 16 , 17 and with organic dyes used in solar cells, 18 which contributed to our current knowledge of charge transfer in model metal/TiO 2 (110) systems, 19 including Pt 20 and small Pt clusters.…”
Section: Introductionmentioning
confidence: 99%
“…13,20,[23][24][25] To improve the performance of existing catalysts and photocatalysts, a detailed understanding of all the factors that can affect their activity is crucial. To this end, numerous theoretical and experimental studies have examined the interaction between the metal NPs and oxide surfaces, 9,[26][27][28] as well as the mechanisms of nucleation, growth, and diffusion of supported metal NPs. [29][30][31] As a typical reducible oxide, TiO 2 usually contains "excess" electrons (i.e., electrons in excess of those that a) Author to whom correspondence should be addressed.…”
Section: Introductionmentioning
confidence: 99%
“…47 Furthermore, well-known size and support effects in transition metal catalysis have motivated NC-AFM experiments on Pt atoms on TiO 2 (110). 46 Results have revealed that isolated Pt atoms exhibit the highest chemical interaction with the probing tip for all tip apexes under consideration, thereby illustrating the high chemical reactivity of metal atoms on metal oxide substrates compared with other sites (Figure 7). …”
Section: Imaging and Spectroscopy Of Adsorbatesmentioning
confidence: 93%
“…42−45 Additionally, individual metal atoms have been recently imaged and characterized on supports such as TiO 2 (110). 46 The main advantage provided by NC-AFM over STM is the ability to clearly distinguish different adsorbates and surface atoms via force spectroscopy. Imaging and spectroscopy experiments performed on rutile TiO 2 (110) are particularly illustrative in this case, where it was demonstrated via a combination of site-specific force spectroscopy experiments and ab initio calculations that characteristic force−distance relationships for adsorbed OH groups and Ti as well as O atoms on the surface can be reliably determined for different tip apex models.…”
Section: Imaging and Spectroscopy Of Adsorbatesmentioning
confidence: 99%